Praktek Perkawinan Beda Agama Perspektif Undang-Undang Perkawinan dan Hukum Islam (Studi Analisis Perkawinan di Kecamatan Kutalimbaru Deli Serdang) - Nasution, Evriza Noverda; Tanjung, Dhiauddin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Marriage is the basis of community life, the union between a man and a woman in the holy bond of marriage is the first step in the life of husband and wife to grow and develop in a life called a family. The occurrence of a marriage between a man and a woman is certainly based on a sense of affection and love where two people with different life backgrounds unite and live together to form a family. The feeling of love knows no religion, the feeling just grows and develops which sometimes becomes a difference between two people who make a marriage, the existence of an interfaith marriage in society often occurs and is carried out where both religion and law have prohibited the practice of interfaith marriage itself. Interfaith marriage is one of the deviant marriages in Indonesia, this paper is an explanation of one of the deviant marriages in Indonesia seen from the view of Law no. 1 of 1974 and also KHI Analysis of Marriage Practices in Namo Mirik Village, District. Kutalimbaru, where the majority of the population is Christian and the Muslim population is only a small part of the community, so that when there is a desire to marry from couples of different religions and each wants to stay in their religion, then interfaith marriage is what they choose to unite the couple. In this study, the method used is a socio-legal method where the research used in addition to using statutory analysis, social sciences and anthropology also become supporters in the discussion of this research. The results of the research conducted that the practice of interfaith marriage is one of the alternative marriages that couples choose in Namomirik village, Kutalimbaru sub-district, Deli Serdang. This happens because of the strong customs used in the village, customary law takes precedence over religious and state law.